Paleobiodiversity and tectono-sedimentary records in the Mediterranean Tethys and related eastern areas: proceedings of the 1st Springer Conference of the Arabian Journal of Geosciences (CAJG-1), Tunisia 2018 - Boughdiri, Mabrouk; Bádenas, Beatriz; Selden, Paul A.; Jaillard, Etienne; Bengtson, Peter; Granier, Bruno R.C. (Advances in Science, Technology & Innovation, IEREK Interdisciplinary Series for Sustainable Development, 2019)
This edited volume contains the best papers accepted for presentation during the 1st Springer Conference of the Arabian Journal of Geosciences (CAJG-1), Tunisia 2018. The volume shares the latest results from paleontological, biostratigraphic and sedimentological studies by experienced researchers mainly from research institutes in the Mediterranean and Middle East. Main topics include: paleontology, biostratigraphy, sedimentology, paleoclimatology and geomorphology. Some new insights are given on paleobiodiversity and major biological tools for biostratigraphy, patterns, mechanisms and processes of meso-cenozoic sedimentation in the Mediterranean and Middle East. In particular, case studies are included to highlight the major controlling factors of Tethyan biosphere-geosphere interactions as inferred from the Mediterranean and Middle East regions. The book is of interest to all researchers in the fields of different disciplines involved in the sedimentary geology